Kesan moderasi iklim beretika terhadap hubungan antara kepimpinan transformasi, personaliti Big-5 dan integriti - Mariah, Darus @ Mat Junus (2022)
Integrity in public service is crucial to create efficient administration and services through the application of good values. This also ensures the people's determination and trust in the services provided by civil servants. However, complaints received by the Public Complaints Bureau, shows that the services provided by various government agencies are still less satisfactory. Based on previous studies, there are several factors that influence the practice of integrity, namely leadership, individual and environmental factors. This study examines the moderating effect of ethical climate on the relationship between transformational leadership, Big-5 personality, and integrity. Transformational Leadership Theory and Trait Activation Theory acts as the underlying theories to explain the studied phenomenon. This quantitative study involved 131 government officials under Kedah state and was determined via purposive sampling method. Statistical Product and Service Solutions (SPSS IBM) 25 software system and Partial Least Squares Structural Equation Modeling (PLS-SEM) version 3 were used to analyze the data. The results of the study show that transformational leadership, agreeable personality, conscientiousness personality, and ethical climate have a significant relationship with integrity. Nevertheless, there is no significant relationship between extraversion personality, emotional stability personality, and openness personality with integrity. In fact, the moderating effect of ethical climate on the relationship between transformational leadership and Big-5 personality with integrity also did not have a significant relationship. The findings of this study are expected to help future researchers to understand the moderating effect of ethical climate on the relationship between transformational leadership and Big-5 personality with integrity.